Sustained ICP Elevation Is a Driver of Spatial Memory Deficits After Intraventricular Hemorrhage and Leads to Activation of Distinct Microglial Signaling Pathways - Chloe H. Puglisi; Bradley P. Ander; Catherine Peterson; Janet A. Keiter; Heather Hull; Cameron W. Hawk; Venina S. Kalistratova; Ali Izadi; Gene G. Gurkoff; Frank R. Sharp; Ben Waldau (Translational Stroke Research, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Molecular Correlates of Hemorrhage and Edema Volumes Following Human Intracerebral Hemorrhage Implicate Inflammation, Autophagy, mRNA Splicing, and T Cell Receptor Signaling - Marc Durocher; Bodie Knepp; Alan Yee; Glen Jickling; Fernando Rodriguez; Kwan Ng; Xinhua Zhan; Farah Hamade; Eva Ferino; Hajar Amini; Paulina Carmona-Mora; Heather Hull; et al. (Translational Stroke Research, 2021)
Intracerebral hemorrhage (ICH) and perihematomal edema (PHE) volumes are major determinants of ICH outcomes as is the immune system which plays a significant role in damage and repair. Thus, we performed whole-transcriptome analyses of 18 ICH patients to delineate peripheral blood genes and networks associated with ICH volume, absolute perihematomal edema (aPHE) volume, and relative PHE (aPHE/ICH; rPHE). We found 440, 266, and 391 genes correlated with ICH and aPHE volumes and rPHE, respectively ( p < 0.005, partial-correlation > |0.6|). These mainly represented inflammatory pathways including NF-κB, TREM1, and Neuroinflammation Signaling—most activated with larger volumes. Weighted Gene Co-Expression Network Analysis identified seven modules significantly correlated with these measures ( p < 0.05). Most modules were enriched in neutrophil, monocyte, erythroblast, and/or T cell-specific genes. Autophagy, apoptosis, HIF-1α, inflammatory and neuroinflammatory response (including Toll-like receptors), cell adhesion (including MMP9), platelet activation, T cell receptor signaling, and mRNA splicing were represented in these modules (FDR p < 0.05). Module hub genes, potential master regulators, were enriched in neutrophil-specific genes in three modules. Hub genes included NCF2, NCF4, STX3, and CSF3R, and involved immune response, autophagy, and neutrophil chemotaxis. One module that correlated negatively with ICH volume correlated positively with rPHE. Its genes and hubs were enriched in T cell-specific genes including hubs LCK and ITK, Src family tyrosine kinases whose modulation improved outcomes and reduced BBB dysfunction following experimental ICH. This study uncovers molecular underpinnings associated with ICH and PHE volumes and pathophysiology in human ICH, where knowledge is scarce. The identified pathways and hub genes may represent novel therapeutic targets.

HDAC9 Polymorphism Alters Blood Gene Expression in Patients with Large Vessel Atherosclerotic Stroke - Natasha Shroff; Bradley P. Ander; Xinhua Zhan; Boryana Stamova; DaZhi Liu; Heather Hull; Farah R. Hamade; Cheryl Dykstra-Aiello; Kwan Ng; Frank R. Sharp; Glen C. Jickling (Translational Stroke Research, 2019)

Biomarkers of Acute Stroke Etiology (BASE) Study Methodology - Edward C. Jauch; Andrew D. Barreto; Joseph P. Broderick; Doug M. Char; Brett L. Cucchiara; Thomas G. Devlin; Alison J. Haddock; William J. Hicks; Brian C. Hiestand; Glen C. Jickling; Jeff June; David S. Liebeskind; et al. (Translational Stroke Research, 2017)

Improving the translation of animal ischemic stroke studies to humans - Glen C. Jickling; Frank R. Sharp (Metabolic Brain Disease, 2015)

Heat Shock Proteins in the Brain: Role of Hsp70, Hsp 27, and HO-1 (Hsp32) and Their Therapeutic Potential - Frank R Sharp; Xinhua Zhan; Da-Zhi Liu (Translational Stroke Research, 2013)

Excitatory and Mitogenic Signaling in Cell Death, Blood–brain Barrier Breakdown, and BBB Repair after Intracerebral Hemorrhage - Da-Zhi Liu; Frank R. Sharp (Translational Stroke Research, 2012)

Gene Expression Profiling of Blood in Brain Arteriovenous Malformation Patients - Shantel M. Weinsheimer; Huichun Xu; Achal S. Achrol; Boryana Stamova; Charles E. McCulloch; Ludmila Pawlikowska; Yingfang Tian; Nerissa U. Ko; Michael T. Lawton; Gary K. Steinberg; Steven D. Chang; Glen Jickling; et al. (Translational Stroke Research, 2011)

Are Underlying Assumptions of Current Animal Models of Human Stroke Correct: from STAIRs to High Hurdles? - Renée J. Turner; Glen C. Jickling; Frank R. Sharp (Translational Stroke Research, 2011)

Gender-Dependent Correlations of Carotid Intima–Media Thickness with Gene Expression in Blood - Renée J. Turner; Cheryl D. Bushnell; Thomas C. Register; Frank R. Sharp (Translational Stroke Research, 2011)

Correlations Between Gene Expression and Mercury Levels in Blood of Boys With and Without Autism - Boryana Stamova; Peter G. Green; Yingfang Tian; Irva Hertz-Picciotto; Isaac N. Pessah; Robin Hansen; Xiaowei Yang; Jennifer Teng; Jeffrey P. Gregg; Paul Ashwood; Judy Van de Water; Frank R. Sharp (Neurotoxicity Research, 2011)

Correlations of Gene Expression with Blood Lead Levels in Children with Autism Compared to Typically Developing Controls - Yingfang Tian; Peter G. Green; Boryana Stamova; Irva Hertz-Picciotto; Isaac N. Pessah; Robin Hansen; Xiaowei Yang; Jeffrey P. Gregg; Paul Ashwood; Glen Jickling; Judy Van de Water; Frank R. Sharp (Neurotoxicity Research, 2011)

Where Do Omics and Markers Go Next? - Frank R. Sharp (Translational Stroke Research, 2010)